(untitled) (Research, Society and Development, 2020)
Objective: to develop a protocol for attending cardiopulmonary arrest in the hemodialysis unit to be used by health professionals. Method: exploratory, qualitative study, using Convergent-Assistance Research as a method. The setting was a hospital in the state of Rio de Janeiro, where an individual interview was conducted recorded from a semi-structured script with 22 nursing professionals in the hemodialysis sector. The data were analyzed according to the steps proposed by the method, emerging the category guiding care: elaboration of a Standard Operational Protocol on cardiorespiratory arrest in hemodialysis. Results: professionals do not feel safe to act in a cardiopulmonary arrest during hemodialysis, as they reported that the necessary supplies and periodic training are lacking, hindering the safe care provided to the patient. Final considerations: the Operational Protocol will serve as a guide for good care practices that should be performed at the time of cardiorespiratory arrest during hemodialysis.